PLIOCENE AND PLEISTOCENE DEPOSITIONAL ENVIRONMENTS IN THE PESCULUSE AREA (SALENTO, ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
An integrated sedlmentologic and palaeoecologic approach is used to define the evolving Pliocene, Early and Middle Pleistocene depositional environments in the Pesculuse area. Lower Pliocene deposits show evidence of a quiet outer-shelf setting, apparently not affected by the physiography of the transgressed palaeotopography. In contrast, the onlap of Upper Pliocene carbonate deposits onto topographic highs testifies that sedlmentation was preceded by a block-faulting event. The Late Pliocene transgression flooded a subaerial karstic landscape. A ridge of Cretaceous limestone created a protected enuronment, In which wavy bedforms of exceptional scale, which are thought to result from tsunami surges, were generated and preserved. At this stage, different palaeocommunities settled in several shallow-water micro-environments.
Keywords: Palaeoenvironments; Pliocene; Pleistocene; Southern Italy.